The Role of E-CRM in Shaping Customer Experience Satisfaction and Loyalty in The Banking Industry - Mamgain, Pradeep; Abed-Ouj, Nibras Kadhim (Breakthroughs Information Technology, 2025)
Objective: This study aims to systematically synthesize the relationship between Electronic Customer Relationship Management (E-CRM), customer experience, customer satisfaction, and customer loyalty in the banking industry. This study addresses the theoretical gap regarding the mediating role of experience and satisfaction in the context of digital banking, as well as identifying areas for further empirical exploration.Research Design & Methods: This study uses a systematic literature review design by analysing national and international journal articles published between 2020 and 2025 on E-CRM in the banking sector. This analysis combines descriptive classification and synthesis to identify key variables, methodological trends, and research gaps related to the relationship between E-CRM, customer experience, satisfaction, and loyalty. Findings: This review shows a consistent positive and significant relationship between E-CRM and customer loyalty, which is largely mediated by customer experience and customer satisfaction across various sectors, indicating that improvements in digital service quality, ease of use, and personalization contribute to a stronger experience and satisfaction, which in turn strengthens loyalty. Additionally, contextual factors such as system quality, security, trust, and relationship quality significantly influence the effectiveness of E-CRM implementation.Implications & Recommendations: These findings theoretically confirm that E-CRM plays a central role in shaping customer experience, satisfaction, and loyalty, and practically recommend that banks develop user-oriented E-CRM through omnichannel integration, improved security, personalization, service quality, and a sustainable feedback system. Contribution & Value Added: This study contributes academically through the integrative framework of E-CRM–experience–satisfaction–loyalty while offering practical value by formulating strategic directions for E-CRM implementation and an agenda for further research.